2012
DOI: 10.1016/j.psychres.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between reward-based learning and nicotine dependence in smokers with schizophrenia

Abstract: Cigarette smoking rates remain remarkably high in schizophrenia relative to smoking in other psychiatric groups. Impairments in the reward system may be related to elevated rates of nicotine dependence and lower cessation rates in this psychiatric group. Smokers with schizophrenia and schizoaffective disorder (SWS; n = 15; M age = 54.87, SD = 6.51, 100% male) and a non-psychiatric control group of smokers (NCL; n = 16; M age = 50.38, SD = 11.52; 93.8% male) were administered a computerized signal detection tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
7
32
0
Order By: Relevance
“…Following prior procedures (Pizzagalli et al, 2005, 2008a,b; Bogdan and Pizzagalli, 2006; AhnAllen et al, 2012), task performance was analysed in relation to four variables: response bias, discriminability, accuracy (i.e., hit rates) and reaction time (RT). Response bias provides an index of the participant’s systematic preference for the stimulus paired with the more frequent reward, and is thus the main variable of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Following prior procedures (Pizzagalli et al, 2005, 2008a,b; Bogdan and Pizzagalli, 2006; AhnAllen et al, 2012), task performance was analysed in relation to four variables: response bias, discriminability, accuracy (i.e., hit rates) and reaction time (RT). Response bias provides an index of the participant’s systematic preference for the stimulus paired with the more frequent reward, and is thus the main variable of interest.…”
Section: Methodsmentioning
confidence: 99%
“…70,71 Two published studies indicated no differences between controls and schizophrenia patients in developing a response bias in the RBPRT. 72,73 A third study indicated slowed response bias development in schizophrenia patients (Erican Duncan, personal communication). The original negative results may be related to the patients smoking status or negative symptom levels.…”
Section: Integrating Reward Feedback For Decision Makingmentioning
confidence: 99%
“…As is the case with many putative endophenotypes for depression, reward learning may not be specific to depression. A recent study found that within a group of schizophrenics those with greater nicotine dependence failed to develop a bias to select the more valued stimuli (AhnAllen et al, 2012). …”
Section: Reward Learningmentioning
confidence: 99%